2018
DOI: 10.1002/pam.22112
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Public Insurance Expansions on Substance Use Disorder Treatment: Evidence from the Affordable Care Act

Abstract: We examine the effect of Medicaid expansion under the Affordable Care Act (ACA) on substance use disorder (SUD) treatment utilization and financing. We combine data on admissions to specialty facilities and Medicaid‐reimbursed prescriptions for medications commonly used to treat SUDs in nonspecialty outpatient settings with an event‐study design. Several findings emerge from our study. First, among patients receiving specialty care, Medicaid coverage and payments increased. Second, the share of patients who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 72 publications
5
59
2
Order By: Relevance
“…59,99 As an increasing number of patients with OUDs have behavioral health insurance coverage, more patients may be accessing care, including in physician offices. 30,100104 However, robust evidence does not yet establish clearly improved behavioral health outcomes attributable to these policy changes, perhaps because further follow-up time is needed. 100 Also, the treatment gap remains because of the growing population of patients with OUDs and persistently low number of providers.…”
Section: Policy Pathways To Increase Buprenorphine Treatment Provisionmentioning
confidence: 99%
“…59,99 As an increasing number of patients with OUDs have behavioral health insurance coverage, more patients may be accessing care, including in physician offices. 30,100104 However, robust evidence does not yet establish clearly improved behavioral health outcomes attributable to these policy changes, perhaps because further follow-up time is needed. 100 Also, the treatment gap remains because of the growing population of patients with OUDs and persistently low number of providers.…”
Section: Policy Pathways To Increase Buprenorphine Treatment Provisionmentioning
confidence: 99%
“…The results of this study are also consistent with research that has examined the impact of Medicaid expansion brought about through implementation of the ACA. For example, a study assessing the impact of Medicaid expansion under the ACA on substance use disorder treatment utilization and financing using TEDS‐A (2010‐2015) found that Medicaid insurance coverage and Medicaid as a form of payment increased in expansion states compared to nonexpansion states . Another study found a rise in opioid treatment admissions in states that expanded Medicaid under the ACA and concluded that this increase was driven by the increase in opioid treatment admissions covered by Medicaid .…”
Section: Discussionmentioning
confidence: 99%
“…TEDS includes facility data from state administrative systems and therefore is impacted by administrative changes that can impact missingness of data. However, we used an approach to excluding missing data similar to that used in previous studies of insurance data in the TEDS‐A, and further attempted to account for this in both primary and sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Among young adults, Medicaid coverage rates increased by about 5 percentage points in 2014 and 9 in 2015 (Wehby and Lyu, 2018). Furthermore, Medicaid coverage was also found to increase substantially for subpopulations of individuals with opioid or other substance abuse issues (Feder et al, 2017;Maclean and Saloner, 2019;Meinhofer and Witman, 2018) as well as individuals with histories of involvement with the criminal justice system Winkelman et al (2016), 3 and those with both history of justice system involvement and substance abuse disorders (Saloner et al, 2016). Furthermore, Medicaid coverage was also found to increase substantially for subpopulations of individuals with opioid or other substance abuse issues (Feder et al, 2017;Maclean and Saloner, 2019;Meinhofer and Witman, 2018) as well as individuals with histories of involvement with the criminal justice system Winkelman et al (2016), 3 and those with both history of justice system involvement and substance abuse disorders (Saloner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Medicaid coverage was also found to increase substantially for subpopulations of individuals with opioid or other substance abuse issues (Feder et al, 2017;Maclean and Saloner, 2019;Meinhofer and Witman, 2018) as well as individuals with histories of involvement with the criminal justice system Winkelman et al (2016), 3 and those with both history of justice system involvement and substance abuse disorders (Saloner et al, 2016). Surprisingly, though, the literature has found mixed results regarding whether the increases in Medicaid coverage for those with substance abuse problems resulted in additional substance addiction treatment (Feder et al, 2017;Maclean and Saloner, 2019;Meinhofer and Witman, 2018;Saloner et al, 2016). Surprisingly, though, the literature has found mixed results regarding whether the increases in Medicaid coverage for those with substance abuse problems resulted in additional substance addiction treatment (Feder et al, 2017;Maclean and Saloner, 2019;Meinhofer and Witman, 2018;Saloner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%